UMP partners with Indian Institute of Technology to address future engineering educational challenges - UMP, PNC (2019)
Uttar Pradesh (India), 7 March- Universiti Malaysia Pahang (UMP) has signed a Memorandum of Understanding (MoU) with the Indian Institute of Technology (IIT) for a period of seven years at the IIT Campus at Varanasi, Uttar Pradesh, India.